2021
DOI: 10.1186/s12887-021-02891-x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of childhood injury and injury severity on school performance and high school completion in Australia: a matched population-based retrospective cohort study

Abstract: Background Exploring the impact of injury and injury severity on academic outcomes could assist to identify characteristics of young people likely to require learning support services. This study aims to compare scholastic performance and high school completion of young people hospitalised for an injury compared to young people not hospitalised for an injury by injury severity; and to examine factors influencing scholastic performance and school completion. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 38 publications
0
6
1
Order By: Relevance
“…A previous analysis that examined all injuries found that young people hospitalised for any type of injury demonstrated a higher risk of not achieving the NMS on both numeracy and reading NAPLAN assessments compared with matched peers who had not been hospitalised for an injury (32). This is in contrast to the current analysis where only young females hospitalised for a burn were identi ed as having a higher risk of not achieving the NMS for reading compared with peers.…”
Section: Discussioncontrasting
confidence: 99%
“…A previous analysis that examined all injuries found that young people hospitalised for any type of injury demonstrated a higher risk of not achieving the NMS on both numeracy and reading NAPLAN assessments compared with matched peers who had not been hospitalised for an injury (32). This is in contrast to the current analysis where only young females hospitalised for a burn were identi ed as having a higher risk of not achieving the NMS for reading compared with peers.…”
Section: Discussioncontrasting
confidence: 99%
“…This is possibly due to factors such as increased physical activity, sports participation, or other school-related activities. 16,17 On a similar note, younger aged students also showed a highly significant association with occurrence of injury. However, no significant association was found between the occurrence of injury and monthly income, the education level of the father, the occupation of the mother, or the number of family members.…”
Section: Discussionmentioning
confidence: 69%
“…Adjusted relative risks (ARRs) and 95% CIs were generated. Variables were included in the model that had previously been associated with school performance5 8 22–25 and forward selection was used to sequentially add covariates to the models, with significance assessed using p values (p<0.05). The final model included burn status, NAPLAN grade (ie, 3, 5, 7 or 9), sex, comorbidity status (Y/N), LBOTE, socioeconomic status of residential area, highest level of education for any parent/guardian (ie, bachelor or higher degree or other), log of hospital LOS and school sector (ie, government, Catholic, independent).…”
Section: Methodsmentioning
confidence: 99%
“…ARR and 95% CIs were calculated. The selection of variables for inclusion in the models was informed by previous studies,5 8 22–25 and forward selection was used to sequentially add covariates, with significance assessed at p<0.05. The final models included burn status, sex, comorbidity status (Y/N), LBOTE, socioeconomic status of residential area, highest level of education for any parent/guardian and geographical location of residence.…”
Section: Methodsmentioning
confidence: 99%